Hubungan Antara Kecemasan dengan Penyesuaian Diri pada Orang-orang Lanjut Usia - Muslimah Zahro Romas (LPPM Universitas Proklamasi 45, 2010)
Objective of this research is to find the influence of anxiety on personal adjustment among elderly. Elderly with high level of anxiety about their present and future well being had difficult experience in their personal adjustment. It was hypothesized that there would be a negative relationship between anxiety and personal adjustment among elderly. The more they felt anxiously, their personal adjustment would be worse. On the other hand, the less they felt anxiously, their personal adjustment would be better. There were 70 elderly aged 56+ participated in this research. They were from Karangwaru Yogyakarta. Two instruments were used i.e. Taylor Manifest Anxiety Scale (T-MAS) and the Personal Adjustment Scale. The product moment correlation statistical analysis revealed that ncy • -.647, p<.000. It meant that the anxiety variable influenced significantly the personal adjustment among elderly. That influence was about 41.8%. It was a warned influence. It was recommended that the Karangwaru local government should provide a convenient place for those elderiy to communicate to each other pleasantly and to consult their physical-psychological-social problems toward some professionals i.e. physician, nutritionist, and psychologist.